Night lights and regional GDP - Frank Bickenbach; Eckhardt Bode; Mareike Lange; Peter Nunnenkamp (Kiel Institute for the World Economy (IfW), 2013)
Night lights could be a valuable proxy of economic activity at the subnational level when GDP data are lacking or of poor quality. Supplementing Henderson et al.'s (2012) analysis at the national level, we assess the stability of the elasticity of GDP with regard to night lights across regions in Brazil, India, the United States, and Western Europe. The relationship between regional GDP and night lights proves to be unstable, not only where regional GDP data may be unreliable but also where such data are of high quality. This suggests that night lights tend to be a poor proxy of regional economic activity.
Keywords: R11; E01; 330; night lights; regional GDP data; stability of lights elasticities; emerging markets; developed economies